Works. - Johnston, Alexandra F., 1939- author.
1 online resource (viii, 353 pages)
Keywords: Collected Studies CS1062 This volume brings together a selection of the major articles of Alexandra F. Johnston, which along with similar volumes by the late David Mills, Peter Meredith and Meg Twycross makes up a set of "Shifting Paradigms in Early English Drama Studies". Alexandra Johnston, the founding director of the research project, Records of Early English Drama, is one of these four key scholars whose work has had a profound influence on the study of medieval and early modern English drama. This collection of essays focuses especially on the York plays: on the Mercers' documents that initiated the project itself; on the theology and christology of the plays; on the relationship between the plays and contemporary administrative bodies, both civic and national; and on the performance of the York plays in modern times. A further group of articles considers documentary evidence for the wide range of drama and mimetic ceremony in the Midlands and the West Country, reinforcing our understanding that these events took place predominately on a local parish level. The collection is rounded out with a survey of the immense changes that our reading of early English drama have undergone over the past half century.